2018
DOI: 10.1073/pnas.1800138115
|View full text |Cite
|
Sign up to set email alerts
|

Formate rescues neural tube defects caused by mutations in Slc25a32

Abstract: Periconceptional folic acid (FA) supplementation significantly reduces the prevalence of neural tube defects (NTDs). Unfortunately, some NTDs are FA resistant, and as such, NTDs remain a global public health concern. Previous studies have identified SLC25A32 as a mitochondrial folate transporter (MFT), which is capable of transferring tetrahydrofolate (THF) from cellular cytoplasm to the mitochondria in vitro. Herein, we show that gene trap inactivation of () in mice induces NTDs that are folate (5-methyltetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 41 publications
1
30
0
1
Order By: Relevance
“…Nonetheless, NTDs remain a significant clinical problem, as more than 30% of NTD affected pregnancies may be FA resistant, accounting for a large number (>400,000 pregnancies per year) of affected infants even in countries that employ mandatory folate fortification of the food supply (Copp et al, 2013). Recently, FA-resistant NTDs were reported to be associated with multiple developmental signaling pathways, including the Wnt/PCP (planar cell polarity; Chen, Lei, Cao et al, 2018;Kharfallah et al, 2017;Kibar et al, 2009;Lei et al, 2010Lei et al, , 2019, sonic hedgehog (Murdoch & Copp, 2010), and mitochondrial folate metabolic pathways (Kim et al, 2018). However, mutations in those pathways have been identified in only a small fraction of NTD cases (Greene & Copp, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, NTDs remain a significant clinical problem, as more than 30% of NTD affected pregnancies may be FA resistant, accounting for a large number (>400,000 pregnancies per year) of affected infants even in countries that employ mandatory folate fortification of the food supply (Copp et al, 2013). Recently, FA-resistant NTDs were reported to be associated with multiple developmental signaling pathways, including the Wnt/PCP (planar cell polarity; Chen, Lei, Cao et al, 2018;Kharfallah et al, 2017;Kibar et al, 2009;Lei et al, 2010Lei et al, , 2019, sonic hedgehog (Murdoch & Copp, 2010), and mitochondrial folate metabolic pathways (Kim et al, 2018). However, mutations in those pathways have been identified in only a small fraction of NTD cases (Greene & Copp, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests MFT is the sole MFT, since inactivation of the gene was shown to result in a 98% reduction in the mitochondrial folate pool in CHO cells. 54,55 We found that inactivating this gene in mice results in severe NTDs that can be partially rescued by maternal formate supplementation, but not 5-methyl-THF or other folate species (46). In the mitochondria, THF can be loaded with 1-C units donated from serine via the activity of SHMT2 (the mitochondrial serine hydroxy methyltransferase), from glycine via the glycine cleavage system, and dimethylglycine or sarcosine by DMGDH (dimethylglycine dehydrogenase) and SARDH (sarcosine dehydrogenase), respectively.…”
Section: Interrogation Of High Probability Networkmentioning
confidence: 97%
“…Low levels of metabolically active folate in the embryo can contribute to the risk of having an NTD by inhibiting DNA synthesis and negatively impacting cell proliferation. Genes involved in FA transport and metabolism have been the focus of decades of research investigations conducted as an effort to gain insight into how FA protects embryos from developingNTDs 46,47. For example, the gene encoding for the methylenetetrahydrofolate reductase (MTHFR) enzyme, was among the first candidate genes believed to be a risk factor for NTDs.…”
mentioning
confidence: 99%
“…It is known, for example, that the yeast NAD + carrier transports FAD to some extent [165]. In addition, the physiological importance of SLC25A32 has been emphasized by gene-trap inactivation experiments of SLC25A32 in mice displaying neural tube defects and embryonal death [166]. One might speculate that both reduced mitochondrial FAD and folate transports would lead to mitochondrial defects underlying the symptoms of malfunctioning SLC25A32.…”
Section: Slc25a32 Deficiencymentioning
confidence: 99%